Psychometric Properties of the Death Anxiety Beliefs and Behaviors Scale: A Methodological Study in Türkiye - Yildiz, Esra; Ozturk, Zeynep; Turan, Gulcan Bahcecioglu (Springer, 2026)
Death anxiety is a multidimensional construct encompassing emotional, cognitive, and behavioral responses to mortality. In societies like T & uuml;rkiye, where cultural and spiritual values significantly shape the perception of death, valid measurement tools are essential for understanding how individuals experience these concerns. The Death Anxiety Beliefs and Behaviors Scale (DABBS) is a comprehensive instrument capturing these dimensions; however, no validated Turkish version has been available. This study aimed to adapt the DABBS into Turkish and evaluate its structural validity and reliability among adults in T & uuml;rkiye. A methodological and cross-sectional study design was employed with data collected from 195 adults across different regions of T & uuml;rkiye. Participants completed an online survey including a Descriptive Form and the 18-item Turkish version of the scale (DABBS-T). Translation and cultural adaptation followed international guidelines. Construct validity was assessed through confirmatory factor analysis (CFA), and reliability was evaluated using Cronbach's alpha and test-retest stability. CFA supported the original three-factor structure of the scale-emotion, belief, and behavior-with factor loadings ranging from 0.530 to 0.940. The model demonstrated acceptable fit indices (chi 2/df = 2.00, RMSEA = 0.072, CFI = 0.97, TLI = 0.97). Internal consistency was high across all subscales (Cronbach's alpha = 0.849-0.932). Test-retest reliability coefficients ranged from 0.903 to 0.947, indicating strong temporal stability. No item removal or structural modification was required, suggesting that the Turkish version retained the theoretical integrity of the original instrument. The DABBS-T is a valid and reliable tool for assessing death-related beliefs and behaviors among Turkish adults. Given the scale's strong psychometric performance, it is highly suitable for research and clinical settings, particularly in exploring the intersection of spiritual beliefs and psychological health. It facilitates cross-cultural comparisons and contributes to a broader understanding of death anxiety within diverse cultural frameworks.
Keywords: Validity; Reliability; Death Anxiety Beliefs And Behaviors Scale; T & Uuml;Rkiye; Nursing; Spiritual Health